BST1 regulates nicotinamide riboside metabolism via its glycohydrolase and base-exchange activities - Keisuke Yaku (Nature Portfolio, 2021)
Nicotinamide riboside (NR) is a NAD + precursor exhibiting beneficial effects against aging. Here the authors demonstrate that orally administered NR increases NAD + levels in a diphasic manner and that bone marrow stromal cell antigen 1 plays a crucial role for NAD + synthesis from NR.